PEMBERDAYAAN BAGI PEREMPUAN PENGRAJIN KAIN TENUN SONGKET DI DESA LIMBANG JAYA KECAMATAN TANJUNG BATU KABUPATEN OGAN ILIR - Apriani, Anggun; Nurwahyuliningsih, Eka; Pusnita, Indah; Sutanda, Diki (Aktivasi: Jurnal Pemberdayaan Masyarakat, 2022)
Empowerment activities are an approach to increasing the abilities and potential of women songket woven cloth craftsmen to be more empowered, such as increasing skills, increasing market access, and encouraging progress in socio-economic conditions. The findings of the FGD results were that there were still obstacles in product marketing, so community service activities were carried out in the form of training and assistance with marketing and promotional strategies to increase the value and quality of the products produced so that they could drive increased economic income. The aim of this service activity is to encourage women to participate actively in decision making, as well as to increase the selling value of songket woven cloth by using profitable marketing strategies to improve welfare. Empowerment activities consist of three stages, including the planning stage, implementation stage and monitoring and evaluation. The marketing strategy carried out by the community consists of 1). Creating brand identity; 2). Attend training and workshops; 3). Collaborate with designers; 4). Digital marketing; 5). Take part in exhibitions and events. Thus, this service activity provides positive value for the community and motivates craftsmen to be independent and able to carry out marketing activities in a sustainable manner so that songket woven cloth products can be massively recognized not only by domestic consumers but also abroad.